Predictors of nephrectomy in high grade blunt renal trauma patients treated primarily with conservative intent - Narla Hari Prasad (Indian Journal of Urology, 2014)
Introduction: There is no consensus on the optimal management of high grade renal trauma. Delayed surgery increases the likelihood of secondary hemorrhage and persistent urinary extravasation, whereas immediate surgery results in high renal loss. Hence, the present study was undertaken to evaluate the predictors of nephrectomy and outcome of high Grade (III-V) renal injury, treated primarily with conservative intent. Materials and Methods: The records of 55 patients who were admitted to our institute with varying degrees of blunt renal trauma from January 2005 to December 2012 were retrospectively reviewed. Grade III-V renal injury was defined as high grade blunt renal trauma and was present in 44 patients. The factors analyzed to predict emergency intervention were demographic profile, grade of injury, degree of hemodynamic instability, requirement of blood transfusion, need for intervention, mode of intervention, and duration of intensive care unit stay. Results: Rest of the 40 patients with high grade injury (grade 3 and 4 )did not require emergency intervention and underwent a trail of conservative management. 7 of the 40 patients with high grade renal injury (grade 3 and 4), who were managed conservatively experienced complications requiring procedural intervention and three required a delayed nephrectomy. Presence of grade V injuries with hemodynamic instability and requirement of more than 10 packed cell units for resuscitation were predictors of nephrectomy. Predictors of complications were urinary extravasation and hemodynamic instability at presentation. Conclusion: Majority of the high grade renal injuries can be successfully managed conservatively. Grade V injuries and the need for more packed cell transfusions during resuscitation predict the need for emergency intervention.